The role of religion and social capital on entrepreneurship self-efficacy and motivation among students in Indonesia - Junaidi Junaidi; Suhardi M. Anwar; Sahrir Sahrir (Cogent Business & Management, 2023)
The number on unemployment among developing countries need to be solution among education stakeholders. Some scholar offered some solutions; however, religion and social capital is still need to confirm on social and business context among students. This research investigates how religiosity influences students structural, cognitive, and relational social capital, which subsequently influences entrepreneurship self-efficacy and entrepreneurship motivation. The sample consists of 825 participants were invited in this study. Structural equation modelling (SEM) was used to examine the research hypotheses. Religion has a positive role in influencing students social capital. The association between religiosity and students entrepreneurship self-efficacy and entrepreneurship motivation is also partially mediated by structural, cognitive, and relational social social capital. Only Indonesian Muslim students were included in this study. Future research is therefore required to examine cross-regional, cultural, demographic, and religious factors. Education stakeholders must develop students spirituality and social capital to foster fruitful engagement and communication. They must also educate from both a business and academic standpoint. The social capital and social cognitive theories are strengthened by this study.
Keywords: 650; entrepreneurship; religiosity; social capital; students